Memorandum of understanding between Universiti Teknologi MARA and Jamal Mohamed College / Fakulti Perladangan dan Agroteknologi - Universiti Teknologi MARA, Fakulti Perladangan dan Agroteknologi (Universiti Teknologi MARA (UiTM), 2020)
Memorandum of understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.